Figues de Barbarie and French Figs: Hybridity in the Beur imaginary - Nagy-Zekmi, Silvia (Verbum – Analecta Neolatina, 2014)
The article analyzes the multiple meanings of the border as a textual construct in Beur writing represented by Leila Sebbar, Azouz Begag, Leila Houari, Farida Belghoul by focusing on hybridity as a theoretical tool in the representation of the collective identity of the Beur defined by migration through discourses that emerge from unequal power relations in loci of cultural contact.